Combining magnetic field induced locomotion and supramolecular interaction to micromanipulate glass fibers toward assembly of complex structures at mesoscale - Cheng, Mengjiao (Langmuir : the ACS journal of surfaces and colloids, 2011)
The formation of ordered complex structures is one of the most challenging fields in the research of biomimic materials because those structures are promising with respect to improving the physical and mechanical properties of man-made materials. In this letter, we have developed a novel approach to fabricating complex structures on the mesoscale by combining magnetic-field-induced locomotion and supramolecular-interaction-assisted immobilization. We have employed a magnetic field to locomote the glass fiber, which was modified by the layer-by-layer self-assembly of magnetic nanoparticles, to desired positions and have exploited the supramolecular interaction to immobilize glass fiber onto the appointed position. By magnetically induced micromanipulation, we can drive another fiber across the former one and finally obtain a crossing structure, which can lead to more complex structures on the mesocale. Moreover, we have constructed a mesoscale structure, termed "CHEM", to demonstrate further the application of this method